Firm Value in Profitability, Leverage, Capital Structure, and Firm Growth - Larasati, Sonnia Dea; Betharia, Chintia (Jurnal Akuntansi, 2024)
Abstract Purpose - This research was conducted to determine and explain how profitability, leverage, capital structure, and company growth can affect firm value. Design/methodology/approach - This research used quantitative data with sampling method and the data source was obtained from the annual report of the Automotive and Component Sub Sector companies that have been registered on Indonesian Stock Exchange in 2016-2022. These data in this research are analyzed with panel data regression analysis which is processed using EViews 12 software. Findings - Results from this research point out that profitability, leverage, capital structure, and company growth simultaneously influence company value. The partial test shows profitability with capital structure positively influencing company value. Meanwhile, leverage and company growth have no effect on firm value. Research limitations/implications - The implication from this research, it can assist companies in managing and using leverage properly and optimizing company growth so that stock prices remain stable so that it can be used as a good consideration for investors. Keywords: Company Value, Profitability, Leverage, Capital Structure, and Company Growth